The Effectivity Study: Implementation of the Physics e-Module with PjBL-STEM Model to Describe Students' Creative Thinking Skills and Learning Motivation Profile - N. R. Millen; S. Supahar (Journal of Science Education Research, 2023)
This research focuses on developing and implementing the Physics e-Module PjBL-STEM Model to improve the creative thinking skills and learning motivation of grade X students in straight-motion topics discussion. The purpose of this development research is to 1) Produce a feasible Physics e-Module PjBL-STEM Model. 2) Knowing the effectiveness of the implementation of the Physics e-Module PjBL-STEM Model in order to improve students' creative thinking skills and learning motivation. 3) Describe the students' creative thinking skills and learning motivation profile. The e-module development procedure in this study adapted the Research and Development (RD) method using the ADDIE model developed by Dick and Carry (1996). The subjects of this study were first-grade high school students who used the 2013 curriculum at a school in the city of Yogyakarta. The results of the study show that: 1) The Physics e-Module PjBL-STEM Model is feasible to use in physics learning based on the assessment of experts and practitioners. 2) Implementation of the Physics E-Module PjBL-STEM Model is effective in increasing students' creative thinking skills by 85% and students' learning motivation by 68% which is in the good category. 3) The students' creative thinking ability profile was 54.16%, while the students' learning motivation was 60.41%. Both have average and above-average values. Students with the ability to think creatively and have the motivation to learn above the average are most students who use the Physics e-Module PjBL-STEM Model in physics learning.